Controlled bistability of cold Rydberg excitation with Doppler broadening. (8th February 2019) - Yang, Hui; Fan, Chu-Hui; Zhang, Han-Xiao; Liu, Yi-Mou; Wu, Jin-Hui
Abstract: We study in theory the single-photon Rydberg excitation in an ensemble of two-level cold atoms at finite low temperatures. Rydberg population plotted against laser detuning may exhibit a nonlinear bistable behavior arising from the dipole–dipole interactions manifested as a van der Waals (vdW) potential. We find that Doppler broadening can result in a remarkable reduction of the bistable region, which may disappear as the atomic temperature increases to a certain value, of the order of tens to hundreds of μ K. This special temperature, depending critically on the vdW potential, can be largely raised by partially eliminating the Doppler effect, when a double-photon excitation scheme is used to replace the single-photon excitation scheme.